2005
DOI: 10.1016/j.rmed.2005.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training in adults with chronic obstructive pulmonary disease: A systematic review

Abstract: The purpose of this study was to conduct a systematic review to determine the effect of inspiratory muscle training (IMT) on inspiratory muscle strength and endurance, exercise capacity, dyspnea and quality of life for adults with chronic obstructive pulmonary disease (COPD). A systematic review of the literature was conducted according the Cochrane Collaboration protocol using Medline and CINAHL. Nineteen of 274 extracted articles met the inclusion criteria and addressed comparisons of interest which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 25 publications
6
81
1
3
Order By: Relevance
“…Respiratory muscle function has been shown to contribute to dyspnea, exercise limitation, [23][24][25][26] Furthermore, trials in interstitial lung disease and pulmonary hypertension showed improved exercise capacity, symptoms and quality of life following pulmonary rehabilitation with or without respiratory muscle training. [27][28][29] Marcisz et al 30 showed that FVC, forced expiratory volume in one second, VC, MVV, maximum midexpiratory flow rate 25-75%, and peak expiratory flow rate values were significantly decreased in SSc patients compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory muscle function has been shown to contribute to dyspnea, exercise limitation, [23][24][25][26] Furthermore, trials in interstitial lung disease and pulmonary hypertension showed improved exercise capacity, symptoms and quality of life following pulmonary rehabilitation with or without respiratory muscle training. [27][28][29] Marcisz et al 30 showed that FVC, forced expiratory volume in one second, VC, MVV, maximum midexpiratory flow rate 25-75%, and peak expiratory flow rate values were significantly decreased in SSc patients compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] This effect on respiratory muscle function was shown to be greater compared with whole-body exercise training (cycling or running). 18 In addition to improving respiratory muscle capacity, respiratory muscle training has also been shown to reduce the perception of adverse respiratory sensations and to increase the exercise performance in healthy subjects [19][20][21] as well as in patients with impaired lung function.…”
Section: Introductionmentioning
confidence: 97%
“…18 In addition to improving respiratory muscle capacity, respiratory muscle training has also been shown to reduce the perception of adverse respiratory sensations and to increase the exercise performance in healthy subjects [19][20][21] as well as in patients with impaired lung function. 15,17,22,23 Whether respiratory muscle training in obese patients may also improve respiratory muscle capacity, reduce dyspnea and increase exercise tolerance remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that the mean FEF 0.2-1.2% , FEF 25-75% , FEF 75-85% , MEF 75% and MEF 50% values were significantly higher in both groups after treatments and there were statistically significant differences between mean values of the investigated parameters in group (A) and group (B) after treatment (Table 1, 2 and 3).The results of this study were in concordance with previous studies demonstrating that in welding workers, the improvement in small airway ventilation in welders after diaphragmatic breathing exercise, aerobic exercise training in addition to laser acupuncture therapy might be related to broncholytic effect, disappearance of inflammatory changes in bronchial mucosa, improved potency of airways and respiratory muscles strength. Diaphragmatic breathing exercise is associated with improvement in inspiratory muscles strength and endurance that may help to relieve the sensation of dyspnea (13). Also, diaphragmatic breathing enhances lower lung ventilation, reduces residual volume, improves airflow in small airways and as a result reduces pulmonary hyperinflation in patients with chronic obstructive lung disease (14).…”
Section: Discussionmentioning
confidence: 99%